Performance indicators defining goal scoring opportunities in elite asian beach soccer: an artificial neural network approach - Musa, Rabiu Muazu (Tanjung Malim, 2021)
Performance indicators defining goal scoring opportunities in elite asian beach soccer: an artificial neural network approach by Musa, Rabiu Muazu